Indoor tanning and poor mental health among adolescents in New York City (2015). (May 2021) - Basch, Corey H; Hillyer, Grace C; Kecojevic, Aleksandar; Ku, Cyril S; Basch, Charles E
This study explored relationships between mental health and indoor tanning among high school students in New York City using 2015 data from the Youth Risk Behavior Surveillance System. Those more likely to use indoor tanning were females (odds ratio = 6.26, 95% confidence interval = 6.08–6.45) and non-Hispanic White (odds ratio = 1.10, 95% confidence interval = 1.06–1.14). Being bullied on school property (odds ratio = 1.30, 95% confidence interval = 1.25–1.34), having attempted suicide (odds ratio = 2.08, 95% confidence interval = 1.99–2.18), and having sought counseling (odds ratio = 1.22, 95% confidence interval = 1.18–1.26) were significantly associated with indoor tanning. This study indicates that engaging in indoor tanning is associated with a number of mental health factors.